(untitled) (Research, Society and Development, 2021)
Sweet’s syndrome (SS) is a rare systemic inflammatory condition, which is characterized by the sudden appearance of erythemoedematous cutaneous plaques and nodules, related to systemic symptoms and infiltration of mature neutrophils in histopathological studies. Currently, the disease is classified into three categories: classic (idiopathic), associated with malignancy and drug-induced, and the classic constitutes the majority of cases. In this context, we present a case of a 72-year-old man with a typical picture of the classic form of Sweet’s Syndrome, where he presented regression of the lesions after 2 weeks of treatment, and in these cases the regression starts 72 hours after the start of corticosteroid therapy. systemic. Despite Sweet’s Syndrome being a rare disease, with the diagnosis and proper therapeutic establishment and with the use of systemic corticotherapy, the results end up being extremely fast and favorable to its patients. Therefore, the diagnosis and classification of the form of Sweet’s Syndrome provides an adequate therapeutic direction, considering that in cases in which they are induced by drugs or associated with cancer, there are only satisfactory and lasting therapeutic responses, when the treatment is carried out. of the underlying disease and discontinuation of the causative drug, respectively.